2021
DOI: 10.1002/qj.4124
|View full text |Cite
|
Sign up to set email alerts
|

Heavy versus extreme rainfall events in southeast Australia

Abstract: Focussing on the major cities of Brisbane, Sydney, and Melbourne in southeast Australia, this study seeks to determine the environmental factors that distinguish between heavy rainfall events (HREs) and extreme rainfall events (EREs). Using daily rain gauge observations, HREs and EREs are defined for each domain based, respectively, on the 95th and 99th percentiles of wet‐day rainfall for the period 1979–2018. K‐means clustering is applied to mean sea‐level pressure, data from ERA5 to obtain a set of represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Unlike previous studies of localized Australian rainfall events, which have tended to focus heavily on southern Australia and the eastern coast (e.g., Ashcroft et al, 2019;Avila et al, 2015;Dey et al, 2019Dey et al, , 2021King et al, 2013b;Pepler et al, 2019Pepler et al, , 2021Warren et al, 2021), we extend our focus from the tropics to mid-latitudes and choose three regions of study centered on the cities of Darwin (tropical), Brisbane (subtropical) and Melbourne (mid-latitude, although Melbourne still has some sub-tropical aspects to its climate), respectively. These areas are chosen to develop a methodology that is universally applicable from tropical to mid-latitude regions (given that the findings of Norris et al (2019); Wood et al (2021), indicate the importance of understanding precipitation extremes from the tropics to mid-latitudes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies of localized Australian rainfall events, which have tended to focus heavily on southern Australia and the eastern coast (e.g., Ashcroft et al, 2019;Avila et al, 2015;Dey et al, 2019Dey et al, , 2021King et al, 2013b;Pepler et al, 2019Pepler et al, , 2021Warren et al, 2021), we extend our focus from the tropics to mid-latitudes and choose three regions of study centered on the cities of Darwin (tropical), Brisbane (subtropical) and Melbourne (mid-latitude, although Melbourne still has some sub-tropical aspects to its climate), respectively. These areas are chosen to develop a methodology that is universally applicable from tropical to mid-latitude regions (given that the findings of Norris et al (2019); Wood et al (2021), indicate the importance of understanding precipitation extremes from the tropics to mid-latitudes).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, other studies have attempted to classify the characteristics of extreme weather events by employing methodologies to group extreme rainfall events based on their large‐scale circulation patterns. These studies often employ automated grouping techniques such as K ‐means clustering, principal component analysis, and self‐organizing maps, and have been applied to the study of rainfall extremes across the world including the United States (e.g., Maddox et al., 1979; Swales et al., 2016), Europe (e.g., Allan et al., 2020; Champion et al., 2019; Houssos et al., 2008; Nuissier et al., 2011), China (e.g., Hu et al., 2019), and Australia (e.g., Callaghan & Power, 2014; Fiddes et al., 2015; Fiddes et al., 2021; Pook et al., 2006; Risbey et al., 2013; Speer et al., 2009; Warren et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Melbourne rainfall events also have a strong seasonal cycle with a cool season peak that differs from Brisbane and Sydney, with events most common in July and August, and least common from January to April. Warren et al (2021) similarly found that rainfall events in Brisbane were most common in March and least common in August, rainfall events in Sydney were most common in warmer months, and rainfall events in Melbourne were most common in July and least common in February.…”
Section: Seasonal Event Occurrencementioning
confidence: 85%
“…Gridded data sets can also be created by interpolating rain gauge data. The majority of studies examining heavy rainfall in Australia utilize rain gauges or gridded data sets derived from gauges and focus on how rainfall is affected by climate change (Alexander et al., 2007; Bao et al., 2017; Osburn et al., 2021), climate variability (Ashcroft et al., 2019; Boschat et al., 2015; Dey et al., 2021; Fan et al., 2020; King et al., 2013, 2014, 2020), or synoptic‐scale processes (Fiddes et al., 2015; Pepler et al., 2020; Pook et al., 2014; Warren et al., 2021). The long record period available from rain gauges enables investigation of the long‐term behavior of rainfall in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the easterlies are to some extent lifted orographically as they encounter the Great Dividing Range, which runs parallel to the coastline of the ESB (Speer et al, 2011). Although orography plays a role in the vertical motion required for rainfall in the ESB, dynamically driven ascent and the associated lifting are essential for heavy precipitation and convection (Taschetto and England, 2009; Warren et al, 2021; White et al, 2022).…”
Section: Introductionmentioning
confidence: 99%